2021
DOI: 10.1002/cam4.4081
|View full text |Cite|
|
Sign up to set email alerts
|

HHLA2 deficiency inhibits non‐small cell lung cancer progression and THP‐1 macrophage M2 polarization

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Previous studies have discovered that HHLA2 is overexpressed in gastric cancer, osteosarcoma, clear cell renal cell carcinoma, bladder urothelial cancer, and HCC and is associated with a poor prognosis ( 8 11 ). High HHLA2 overexpression in cancer tissues has been linked to cancer development and malignant characteristics, whereas HHLA2 deficiency inhibits NSCLC cell proliferation, migration, and M2 macrophage polarization ( 12 ). However, HHLA2’s biological functions in liver cancer are yet to be closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have discovered that HHLA2 is overexpressed in gastric cancer, osteosarcoma, clear cell renal cell carcinoma, bladder urothelial cancer, and HCC and is associated with a poor prognosis ( 8 11 ). High HHLA2 overexpression in cancer tissues has been linked to cancer development and malignant characteristics, whereas HHLA2 deficiency inhibits NSCLC cell proliferation, migration, and M2 macrophage polarization ( 12 ). However, HHLA2’s biological functions in liver cancer are yet to be closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…Janakiram et al [ 9 ] demonstrated that HHLA2 is widely expressed in a large proportion of cancer samples such as breast cancer, colon cancer, and prostate cancer. In recent years, studies have shown that HHLA2 participates in the growth and development of a variety of cancers [ 7 , 10 , 11 ]. However, to date, the expression pattern, prognostic significance, and biological function of HHLA2 in cancer have not been elucidated fully.…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, the EGFR/MAPK/ERK signaling pathway was demonstrated to be the mechanism, through which HHLA2 regulated cell proliferation, migration, invasion, and cell cycle. 23 The function of HHLA2 in immune processes has been widely reported, and numerous studies have focused on the role of immune regulation and immune escape in PTC. For example, a previous study identified a variety of dysregulated immune-related genes in PTC and established a risk model predicting the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%